2021
DOI: 10.1007/s00227-021-03912-0
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection and 3D space use partitioning of resident juvenile hawksbill sea turtles in a small Caribbean bay

Abstract: Understanding how aquatic animals select and partition resources provides relevant information about community dynamics that can be used to help manage conservation efforts. The critically endangered hawksbill sea turtle (Eretmochelys imbricata) spends an extended part of its juvenile development in coastal waters. A strong proclivity to remain resident in small areas, often in high density, raises questions about how juveniles partition resources including selection of habitat and spatial overlap among conspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Although the array design and species’ behaviour of our target population are highly specific, the results from this study suggest that acoustic telemetry may be more appropriate for answering fine-scale ecological questions, such as those related to diel and tidal movement patterns, habitat use within highly heterogeneous benthic substrate, or use of discrete habitats for specific behaviours (e.g. resting spots) [ 43 , 61 , 108 110 ]. Acoustic telemetry may also be better suited for studies in constrained water bodies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although the array design and species’ behaviour of our target population are highly specific, the results from this study suggest that acoustic telemetry may be more appropriate for answering fine-scale ecological questions, such as those related to diel and tidal movement patterns, habitat use within highly heterogeneous benthic substrate, or use of discrete habitats for specific behaviours (e.g. resting spots) [ 43 , 61 , 108 110 ]. Acoustic telemetry may also be better suited for studies in constrained water bodies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…When results from S+3 vs S+1 fish were compared and the identified discriminant DE transcripts known to be located in coding areas (668) were matched with those containing DM regions of discriminant value (14,366), only 172 were overlapping (Figure 3A). The over-representation analysis of the list of discriminant DE coding transcripts (668) discerned 442 enriched functions (Gene ontology -Biological process, GO-BP, unique terms; Table S2A).…”
Section: Functional Network Analysis Of Differentially Expressed Tran...mentioning
confidence: 99%
“…2 [12,13], though each target tissue would provide different information on the welfare state and particularly on the timing of the stress response. Likewise, behavioural monitoring is often difficult in the aquatic environment [14,15], but the use of miniaturized data-loggers externally attached to the operculum of sentinel fish represent a practical solution for a continuous and accurate individual tracking of swimming activity and breathing rates in tank-based rearing systems [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that vertical habitat partitioning may occur, which has implications for individuals' access to food and shelter (Makowski et al, 2006;Blumenthal et al, 2009b;Hart et al, 2012;Carrión-Cortez et al, 2013). Further exploration of how depth mediates space use is necessary, but the cost of additional sensors may be a limitation to incorporating this data into acoustic telemetry studies (Matley et al, 2021a).…”
Section: Vertical Space Usementioning
confidence: 99%
“…However, since signals transverse through water easily, acoustic telemetry allows for near-continuous monitoring of marine turtles, who spend 91-97% of their time submerged (Renaud et al, 1995;Schmid et al, 2002), As a result, acoustic telemetry provides higher numbers of detections, improved resolution, and lower positional errors than other tracking techniques, such as satellite telemetry, which only transmits location data when turtles surface (Hazel, 2009;McClellan and Read, 2009;Hart et al, 2012;Whoriskey and Hindell, 2016). Therefore, when within the range of receivers, acoustic telemetry presents an opportunity for effectively collecting spatial information for marine turtles (Matley et al, 2021a;Pillans et al, 2021).…”
Section: Introductionmentioning
confidence: 99%